Moringa oleifera'nın sıçanların parotis bezinde valproik asidin neden olduğu oksidan hasar üzerindeki koruyucu etkisi - YARAT, AYŞEN (My University, 2021)
Valproic acid (VPA) is a broad spectrum anti-epileptic drug that is effective in migraine, bipolar disorder, anxiety and other psychiatric disorders. In addition to many known clinical side effects of VPA, it is stated that it causes sialadenosis and dry mouth, and it is also claimed that VPA treatment prevents the growth of salivary gland tumors.Moringa oleifera Lam. (M. oleifera) is also known as \"miracle tree\" among people because of its healing of various ailments and chronic diseases. Extracts from M. oleifera exhibit multiple nutraceutical or pharmacological functions including anti-inflammatory, anti-oxidant, anti-cancer, hepatoprotective, neuroprotective, hypoglycemic, and blood lipid-reducing functions.In this study, the possible protective effect of M.oleifera alcoholic extract on the parotid gland, which is one of the major salivary glands, was investigated in VPA-treated rats. Parotid gland lipid peroxidation values were significantly increased in the VPA group compared to the control group. Lipid peroxidation values were significantly decreased with the administration of M. oleifera extract.Keywords: Valproic acid, M. oleifera extract, parotid gland, lipid peroxidation
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)